2005
DOI: 10.1016/j.vetimm.2005.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Canine CD20 gene

Abstract: The human CD20 antigen, a 35kDa cell surface nonglycosylated hydrophobic phoshpoprotein is expressed consistently on almost all human B-cells, and its monoclonal antibody is used for the therapy on human B-cell lymphoma. In the present study, canine CD20 gene was cloned and sequenced, and the expression of CD20 mRNA was investigated in canine peripheral blood mononuclear cells (PBMCs), and lymph nodes from healthy dogs, and canine lymphoma cells. Using canine cDNA as a template, full-length of canine CD20 gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…The putative rainbow trout MS4A cDNA isolated from PBLs contained an open reading frame (ORF) of 1319 bp encoding a protein of 305 aa (Figure 5). The predicted amino acid sequence of rainbow trout MS4A revealed four major hydrophobic regions of approximately 22 amino acids, three intracellular and two extracellular domains as predicted for CD20 in mammals [40,41]. The first cytoplasmic region of the protein is longer in rainbow trout, whereas the first loop between helix one and two is extremely small, even smaller than in the human or canine sequence, thus seems unlikely that it can protrude extensively out of the membrane.…”
Section: Resultsmentioning
confidence: 99%
“…The putative rainbow trout MS4A cDNA isolated from PBLs contained an open reading frame (ORF) of 1319 bp encoding a protein of 305 aa (Figure 5). The predicted amino acid sequence of rainbow trout MS4A revealed four major hydrophobic regions of approximately 22 amino acids, three intracellular and two extracellular domains as predicted for CD20 in mammals [40,41]. The first cytoplasmic region of the protein is longer in rainbow trout, whereas the first loop between helix one and two is extremely small, even smaller than in the human or canine sequence, thus seems unlikely that it can protrude extensively out of the membrane.…”
Section: Resultsmentioning
confidence: 99%
“…Two distantly related members, TMEM176A (alias HCA112) 10 and TMEM176B (alias TORID/LR8), 11 , 12 , 13 have been identified in humans on chromosome 7q36.1 and are predicted to share similar topological characteristics to other MS4A members with 10–20% amino‐acid sequence identity 1 . MS4A orthologs have been cloned from other species including the rat, dog, horse and chicken 14 , 15 , 16 , 17 . Although orthologs of the classical tetraspanins have been identified in lower animals such as nematodes, the earliest appearance of MS4A genes have been observed in cartilaginous fish (chondrichthyes), suggesting a more recent gene duplication event for the MS4A family and perhaps a specialized role for these proteins in mammals 3 .…”
Section: Identification Of the Ms4a Protein Familymentioning
confidence: 99%
“…1 MS4A orthologs have been cloned from other species including the rat, dog, horse and chicken. [14][15][16][17] Although orthologs of the classical tetraspanins have been identified in lower animals such as nematodes, the earliest appearance of MS4A genes have been observed in cartilaginous fish (chondrichthyes), suggesting a more recent gene duplication event for the MS4A family and perhaps a specialized role for these proteins in mammals. 3 A number of studies have reported that MS4A genes are expressed as multiple splice variants that are predicted to encode different protein isoforms, 2,18 this being exemplified by the negative regulatory role of the C-terminally truncated MS4A2 expressed on mast cells and basophils 19,20 (see below).…”
mentioning
confidence: 99%
“…Rituximab works by depleting CD20-positive B-cells, largely via antibody-dependent cellular cytotoxicity (ADCC) and complement-dependent cytotoxicity (CDC) (Beers et al, 2010). It has been shown that, as is the case in humans, canine B-cell lymphomas express CD20 but canine T cell lymphomas do not (Jubala et al, 2005;Kano et al, 2005). For this reason, a rituximab-like therapeutic specific to canine CD20 could potentially be effective in treating BCL in dogs.…”
Section: Introductionmentioning
confidence: 99%